Anglican Influence on Old Catholic Liturgy - David R. Holeton; Petr Jan Vinš (Revue Française de Civilisation Britannique, 2017)
Old Catholics have leaned on full communion ties with Anglican churches to create forms of worship which, although decidedly Catholic, are just as decidedly non-Roman, thus strengthening the sense of Old Catholic identity. Full communion, established by the Bonn Agreement of 1931, although slow in making an impact on the life of the two denominations, provided a favourable context for extended liturgical consultations from the 1980s, resulting in Old Catholic use of Anglican liturgical resources in drafting new liturgies. The 1995 Altar Book of the Old Catholic Church in Germany, in particular, owes much to the 1985 Canadian Book of Alternative Services, which had itself borrowed heavily from the 1979 revision of the Book of Common Prayer by the Episcopal Church.